2019
DOI: 10.1111/aji.13082
|View full text |Cite
|
Sign up to set email alerts
|

New models of lipopolysaccharide‐induced implantation loss reveal insights into the inflammatory response

Abstract: Problem Chronic endometritis, inflammation of the uterizzvvne lining caused by common gram‐negative bacterial strains or mycoplasma, has been associated with unexplained implantation failure and infertility. However, limited models of bacteria‐induced implantation loss exist to study the molecular changes that occur in vivo. The goal of this study was to provide a new resource to study the process of bacteria‐induced inflammation and implantation loss utilizing common experimental models: C57Bl/6 mice and prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 88 publications
(144 reference statements)
1
11
0
Order By: Relevance
“…Together, it indicated that implantation accompanies an intricacy inflammatory regulatory net between the blastocysts and maternal uterus, even maternal immune system. Besides, implantation loss in female mice caused by intraperitoneal injection of lipopolysaccharide (LPS) indicates that inflammation changes can impair the inflammatory state of the uterus during the implantation window (Moustafa et al, 2019). In male mice, the SARS-CoV-2 infection could disrupt the blood-testis barrier through the induction of inflammatory cytokines and disruption of junctional protein rather than directly invading the target cells (Peirouvi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Together, it indicated that implantation accompanies an intricacy inflammatory regulatory net between the blastocysts and maternal uterus, even maternal immune system. Besides, implantation loss in female mice caused by intraperitoneal injection of lipopolysaccharide (LPS) indicates that inflammation changes can impair the inflammatory state of the uterus during the implantation window (Moustafa et al, 2019). In male mice, the SARS-CoV-2 infection could disrupt the blood-testis barrier through the induction of inflammatory cytokines and disruption of junctional protein rather than directly invading the target cells (Peirouvi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that implantation failure is induced by LPS through stimulation of the innate immune system and activation of the TLR4 pathway in the early stages of pregnancy [11,33]. A similar study suggested that TLR3 stimulated by a synthetic ligand, poly I: C (which is a double-stranded RNA molecule) in CBA/J female mice increased fetal losses [34] and reduced actin polymerization and adhesion molecule expression in endometrial cells [35].…”
Section: Discussionmentioning
confidence: 92%
“…LPS is an antigen that induces immune responses in uterine endometrial cells by TLR4 activation. LPS can trigger an imbalance in cytokines in the uterine endometrium [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…18 Moustafa showed a new model of LPS-induced implantation loss and found that LPS exposure occurring prior to implantation and decidualization resulted in stark changes in the mouse endometrium. 19 Wu generated a mouse rat model of endometritis induced by the local injection of 40 μg LPS into the uterus; after 48 h, neutrophil counts indicated a significant increase in the mouse endometrium after the injection of 30 or 40 μg LPS. 15 Endometritis is subdivided into two categories: acute endometritis is symptomatic and characterized by microabscess formation and neutrophil invasion in the endometrial superficial epithelium, gland lumina, and uterine cavity, and CE is rather silent without obvious clinical manifestations and is characterized by unusual plasmacyte infiltration into endometrial stromal areas.…”
Section: Discussionmentioning
confidence: 99%